Analisis Kemampuan Bernalar dan Berpikir Kritis (Studi Komparatif antara Accountable Talk dan Higher Order Thinking Skill) - Badridduja, Faiz; Elvida, Sidda; Latipah, Eva (Jurnal Indonesia Sosial Sains, 2022)
This article tries to unravel and reveal two methods that can lead to good conversation, deliver better understanding and develop reasoning and critical thinking skills, namely Accountable Talk and HOTS. The connection with the mind is how neatly arranged words based on good rhetoric can influence thoughts and even give birth to ideas. The purpose of writing this article is to explain the similarities and differences between accountable talk and higher order thinking skills by comparing them. The research method is using library research or library research, both from books and from research journals that are related to the discussion in this study. While the type or nature of this article is comparative descriptive. Accountability is defined as an ethical concept related to the ability to explain the decisions taken and activities carried out alias asked for reasons and accountability. Meanwhile, higher order thinking skills are the ability to connect, manipulate, and change their knowledge and experience critically and creatively in making decisions to solve problems in new situations.